Impact of contrast-distorted image on curvelet coefficients - Ahmed I.T.A.; Chen C.S.D.; Hammad B.T.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Discrete cosine transforms; Image quality; Blocking artifacts; Curvelet Coefficients; Curvelet transforms; Distorted images; Fast fading; High frequency components; Image distortions; Potential features; Image compression